The Effectiveness of Providing Snacks to Nutritional Status of Adolescents - Putri Aulia Arza; Nadia Chalida Nur; Andi Eka Yunianto (Sarana Ilmu Indonesia (salnesia), 2023)
One effort to improve nutritional status is consuming nutritious food and nutrition education for children to instill healthy eating habits from an early age. The purpose of this study was to analyze the effectiveness of providing snacks on the nutritional status and nutritional intake of adolescents. This type of research was a quasi-experimental design with a one-group pre-posttest design without a control group. The research subjects were adolescents aged 11-14 years. Snacks are given for 1 month that meets ± 20% energy and ± 8% protein and ± 15% fat. T-test to analyze the nutritional status of adolescents and nutrient intake before and after giving the distraction food. The results of this study showed that providing distracting food could increase body mass index (p-value=0,000), student weight (p-value=0,000), intake of protein (p-value=0,000), vitamin C (p-value=0,0008), and zinc (p-value=0,0004), but height, carbohydrate intake, and iron intake had no significant effect (p-value>0,05). This study concluded that the provision of snack food effectively increased students' nutritional knowledge, student weight, and intake of protein, vitamin C, and zinc, but height and body mass index, as well as carbohydrates and iron, did not increase significantly. The suggestion from this study is that distraction for adolescents is highly recommended to improve nutritional status so schools should be able to make a policy in providing distracting food as a program to improve adolescent nutrition at school.